Desarrollo psicomotor según género en niños de 4 años de una institución educativa del Callao - Cercado - Otárola Suárez, María Elena (2012)
The purpose of this research is to ascertain the level of psychomotor development in children from an educational institution of the Callao. The research is comparative descriptive. The participants were 50 boys and 50 girls of 4 years. The test was administered Psychomotor Development TEPSI Haeussler Margarita and Teresa Marchant. The results showed that there are significant differences between boys and girls in the three dimensions; coordination, language, and motor. In the dimension coordination the feminine gender obtained 49% in the normal level, and 1% in the level of risk, the masculine gender is ranked in the level of risk with a 22 %, and the levels of delay and normal both with 14 %. In the dimension the feminine gender language gained 46% in the normal level and 4% in the level of risk, while the male gender obtained 39% in the level of delay, 9% in the level of risk and 2% in the normal level. In the dimension motricity the feminine gender obtained 42% in the normal level, 6% in the level of risk and 2% in the level of delay, in the masculine gender obtained 33% in the level of delay and 17% in the level of risk.